Incidence and predictors of preterm neonatal mortality at public hospitals in Eastern Ethiopia: A prospective follow-up study - Teshale Mengesha; Tsegasew Embiale; Dawit Melese; Natnael Dechasa Gemeda; Mickiale Hailu; Aminu Mohamed; Alemu Guta; Yomilan Geneti; Muluken Yigezu; Tewodros Getnet Amera (PLoS ONE, 2025)
Introduction Preterm birth is a major clinical problem, affecting 15 million births every year worldwide. It is the largest cause of death in children under the age of five. Even though different studies have been done regarding the incidence of preterm neonatal death in some parts of Ethiopia, there is a paucity of evidence, especially in the eastern part. Therefore, this study aimed to assess the incidence and predictors of preterm neonatal mortality at public hospitals in eastern Ethiopia from May 1, 2022, to March 30, 2023. Methods An institution-based prospective follow-up study was conducted at public health institutions from May 1, 2022, to March 30, 2023. A structured, pretested, and interviewer-administered questionnaire and checklist were used to collect the data. The data were entered into EpiData version 4.6 and then exported to STATA version 14 for analysis. Kaplan-Meier was used to estimate survival time. A log-rank test was used to compare survival curves between different categories of the explanatory variables. Descriptive analysis, bivariable, and multivariable Cox Proportional Hazards regression analysis were performed. The level of significance was declared at a p-value of <0.05. Results The overall incidence rate of death was 17.03 (14.3, 20.28) per 1000 person-day observations. Mothers’ obstetric complications (AHR: 2.27, 95% CI: (1.46, 3.54)), not crying at birth (AHR: 1.83, 95% CI: (1.09, 2.31)), not immediately initiating breastfeeding (HR: 1.59, 95% CI: (1.10, 2.31)), having sepsis (HR: 1.85, 95% CI: (1.26, 2.72)), having respiratory distress syndrome (HR: 1.98, 95% CI: (1.36, 2.90)), having perinatal asphyxia (HR: 3.1, 95% CI: (2.13, 4.51)), and an APGAR score of less than seven (HR: 2.16, 95% CI: (1.47, 3.16)) were significant predictors of preterm neonatal death. Conclusion This study found the high incidence rate of preterm neonatal mortality, primarily driven by preventable and manageable conditions. Strengthening early identification and timely intervention for the risk factors is critical to improving survival outcomes among preterm neonates.